Implementasi Prinsip Syariah dalam Hotel Syariah: Perspektif Fatwa DSN-MUI dan Maqashid Syariah terhadap Wisata Halal - Ilham Maulana Rahman; Umrotul Khasanah; Aunur Rofiq (STAI Al-Mas'udiyah, 2025)
This study explores the implementation of Sharia principles in a Sharia hotel by focusing on the application of Fatwa DSN-MUI No. 108/DSN-MUI/X/2016 and the integration of Maqashid Syariah values. The research takes a qualitative approach using a case study of Syariah Radho Group in Malang. Data were collected through interviews, observation, and documentation. The findings show that the hotel has adopted several aspects mandated by the fatwa, such as restrictions on immoral conduct, provision of prayer facilities, halal food, and a Sharia-compliant dress code. However, some elements, including formal halal certification and the use of Islamic financial institutions, are not yet fully implemented. The study concludes that while the hotel's practices reflect a genuine commitment to Islamic values, the lack of formal institutional structures and certification hinders full compliance. This article contributes to the discourse on Sharia hotel development and highlights the importance of integrating regulatory fatwas with Maqashid Syariah to support the growth of halal tourism in Indonesia.